OPTIMALISASI KEPITING RAJUNGAN MENJADI PRODUK KERUPUK KEMASAN DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT PESISIR PANTAI KARANGANTU KOTA SERANG - Mohamad Husni; Riyanthi Idayu; As’ari As’ari; Widya Ningsih (Indonesian Collaboration Journal of Community Services, 2022)
This community service departs from a desire to provide skills that can improve the economy in the Karangantu coastal community, Serang City, Banten Province by utilizing marine products in the form of crab crabs so that they are more economically valuable. The benefits of crab crab natural resources can not only be sold individually, especially now that the price of crab crab is very cheap/falling in the market based on the statements of the fishermen of the Karangantu coast. Based on this phenomenon, small crabs are processed into small crab crackers and are suitable for consumption. The method and approach used is problem solving with educational methods which are carried out through lectures, discussions and practice. While the results obtained from this activity are 1) the knowledge and skills of processing small crabs into small crab crackers, 2) The resulting product is in the form of small crab crackers. 3) product packaging is very attractive so that it increases consumer interest in knowing the product and then being able to buy it. The two results above are expected to be able to improve the economy of the Karangantu coastal community, the majority of whom work as fishermen